"La Martella" Split Bowstring Arch Bridge Across Gravina Creek: From Design to Construction. Issue 1 (2nd January 2023) - De Luca, Antonello; Guidi, Laura Giovanna; Matildi, Giuseppe
Abstract: This paper describes the design evolution and construction steps of Gravina (or "La Martella") Bridge, on S.S. 655 "Bradanica" Road, under the authority of the ANAS Department of Potenza, Italy. The final design of the bridge adopted the original solution for a "split" bowstring arch bridge first proposed by Arenas for Barqueta Bridge in 1992. Considering the cultural, historical and environmental heritage of the Gravina prestigious site, the bowstring arch type appeared to be perfectly in line with the contest of "La Martella" bridge. The bridge was re-designed later: the "as-built" solution shows some "adjustments" that were necessary to make bridge construction easier and to improve structural durability. To this end, although the original proportions were preserved, the original "split" arch was replaced by a couple of flanked and converging tubular arches, while a simpler composite deck was used instead of the original steel "boxed-reticular-open section".